2019
DOI: 10.1136/bmj.l5654
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy of antibiotic treatment in patients with chronic low back pain and Modic changes (the AIM study): double blind, randomised, placebo controlled, multicentre trial

Abstract: ObjectiveTo assess the efficacy of three months of antibiotic treatment compared with placebo in patients with chronic low back pain, previous disc herniation, and vertebral endplate changes (Modic changes).DesignDouble blind, parallel group, placebo controlled, multicentre trial.SettingHospital outpatient clinics at six hospitals in Norway.Participants180 patients with chronic low back pain, previous disc herniation, and type 1 (n=118) or type 2 (n=62) Modic changes enrolled from June 2015 to September 2017.I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
111
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 91 publications
(120 citation statements)
references
References 33 publications
4
111
3
2
Order By: Relevance
“…Our results support the main results from the AIM study which detected no clinically important benefit of amoxicillin compared to placebo during 12 months of follow-up. 14 The present cost-utility analysis also extends the findings from the AIM study by demonstrating that the patients in the amoxicillin group used more healthcare than the placebo group. In particular, the use of physiotherapy and manual therapy was substantially higher in the amoxicillin group.…”
Section: Principal Findingssupporting
confidence: 74%
See 1 more Smart Citation
“…Our results support the main results from the AIM study which detected no clinically important benefit of amoxicillin compared to placebo during 12 months of follow-up. 14 The present cost-utility analysis also extends the findings from the AIM study by demonstrating that the patients in the amoxicillin group used more healthcare than the placebo group. In particular, the use of physiotherapy and manual therapy was substantially higher in the amoxicillin group.…”
Section: Principal Findingssupporting
confidence: 74%
“…A placebo controlled randomised trial 10 reported substantial effect of 100 days of high-dosage antibiotic treatment on painrelated disability in patients with chronic LBP and type I Modic changes. The recent AIM replication study 14 from Norway found a small, but not clinically important benefit of amoxicillin vs placebo on pain-related disability for patients with type I or type II Modic changes. In patients with type I Modic changes the benefit was slightly better, but still not clinically important.…”
Section: Introductionmentioning
confidence: 97%
“…Such data were included in articles on spondylarthritis (1)(2)(3)(4)(5), fractures (6), Modic changes (MCs) (7), hemangiomas (8), and pedicle screw loosening (9). However, all but one (6) of these reliability studies had only two observers, most (1,3-5,7-9) had small patient samples (n ¼ [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41], only one (8) included measurements (of signal intensities); the spondylarthritis studies were limited to lesion detection (1)(2)(3)(4)(5). Reliability estimates differed widely in these heterogeneous studies where radiologists and non-radiologists interpreted various fat-suppressed 1.5-T or 3-T series.…”
Section: Introductionmentioning
confidence: 99%
“…The association between MCs and pain is inconsistent (13)(14)(15)(16), but edema type MCs might be symptomatic (17)(18)(19). Mechanical, autoimmune, and infectious explanations for MCs have been proposed (20), and various treatments have been and are being tested (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). Reliable evaluation of the STIR findings is required to validate their relevance to symptoms and treatment (35)(36)(37).…”
Section: Introductionmentioning
confidence: 99%
“…A randomised placebo controlled trial published in 2013 reported that three months of antibiotic treatment offered substantial improvement of symptoms in patients with chronic low back pain and type I Modic changes [4]. The AIM-study (Antibiotics In Modic changes), a reassessment and replication study of the former trial from 2013, did not find any clinically important difference in outcome between the treatment groups at three or 12 months follow-up [5]. There was however a small difference between the groups and an increased variance in outcome measure in the amoxicillin group compared to the placebo group, that may suggest a possible treatment effect in subgroups [6].…”
Section: Introductionmentioning
confidence: 99%